N‐Aryl and N‐Alkyl Carbamates from 1 Atmosphere of CO2. Issue 72 (4th December 2021) - Takeuchi, Katsuhiko; Chen, Ming‐Yu; Yuan, Hao‐Yu; Koizumi, Hiroki; Matsumoto, Kazuhiro; Fukaya, Norihisa; Choe, Yoong‐Kee; Shigeyasu, Shinji; Matsumoto, Seiji; Hamura, Satoshi; Choi, Jun‐Chul
Abstract: We have successfully isolated and characterized the zinc carbamate complex (phen)Zn(OAc)(OC(=O)NHPh) (1 ; phen=1, 10‐phenanthroline), formed as an intermediate during the Zn(OAc)2 /phen‐catalyzed synthesis of organic carbamates from CO2, amines, and the reusable reactant Si(OMe)4 . Density functional theory calculations revealed that the direct reaction of 1 with Si(OMe)4 proceeds via a five‐coordinate silicon intermediate, forming organic carbamates. Based on these results, the catalytic system was improved by using Si(OMe)4 as the reaction solvent and additives like KOMe and KF, which promote the formation of the five‐coordinated silicon species. This sustainable and effective method can be used to synthesize various N‐aryl and N‐alkyl carbamates, including industrially important polyurethane raw materials, starting from CO2 under atmospheric pressure. Abstract : We have isolated and analyzed the reactivity of the key intermediate 1 formed during the Zn(OAc)2 /phen‐catalyzed synthesis of organic carbamates starting from amines, CO2, and Si(OMe)4. The reaction mechanism was analyzed by using DFT. The catalytic system was modified and various N‐aryl and N‐alkyl carbamates that could be used as industrially important polyurethane raw materials were synthesized by using atmospheric CO2 .